Species of the genus Arthrobrachus Solier, 1849 (Coleoptera: Melyridae) distributed to the East of the Andes - Estrada, Patricia M. (Zootaxa, 2016)
The species of the genus Arthrobrachus Solier, 1849 distributed in Argentina, Bolivia, Paraguay and Uruguay have been revised. The morphological study of specimens and the review of the type material have resulted in a new combination: Arthrobrachus flavomarginatus (Blanchard, 1843) n. comb. (from Astylus Laporte, 1836), and four new synonymies: Arthrobrachus rufitarsis Philippi & Philippi, 1864 = A. obscuripes Pic, 1927 n. syn.; Arthrobrachus flavomarginatus (Blanchard, 1843) = A. xanthurus (Blanchard, 1843) n. syn. = A. boucardi Pic, 1919 n. syn. = A. lajoyei Pic, 1919 n. syn. Three species described by Steinheil (1874), Arthrobrachus depressus, Arthrobrachus testaceolimbatus and Arthrobrachus testaceus are considered as incertae sedis and Arthrobrachus quadrilineatus Steinheil, 1874 is transferred to Astylus Laporte, 1836 as A. steinheili nomen novum. Four new species of Arthrobrachus have been described: A. antonioi n. sp., A. eloisae n. sp., A. solervicensi n. sp. and A. armandoi n. sp. Distributional data and a key to the species are provided.